Factores socioculturales que favorecen la presencia de casas maláricas en Intuto y comunidades aledañas, distrito del Tigre, 2025 - Babilonia Zumaeta, Huberth Marcial (2025)
Objective: To identify sociocultural factors associated with the presence of malarial houses in the population of Intuto and surrounding communities in the Tigre district in 2025, considering the household as the epidemiological unit of analysis. Methods: A quantitative, observational, analytical, cross-sectional study was conducted in 373 households in the Tigre district, including indigenous and non-indigenous populations from the Peruvian Amazon. Data were collected using a structured questionnaire administered to the head of household on household conditions, preventive practices, and sociocultural characteristics. Multivariate logistic regression analysis was performed. Results: Of the households evaluated, 122 (32.71%) met the operational definition of a malarial house. Significant associations were observed with inter-community household mobility (OR = 20.19; p = 0.010), bathing after 5:00 p.m. (OR = 3.14; p = 0.006), and a low ratio of insecticide-treated mosquito nets per household (0.0–0.4) (OR = 10.06; p < 0.01). In addition, inadequate attitudes (OR = 36.19; p < 0.001) and preventive practices (OR = 16.21; p < 0.001) were associated with malarial houses, while access to piped sewage showed a protective effect (OR = 0.29; p = 0.024). Conclusion: The presence of malarial houses is associated with sociocultural and structural factors that converge within the household environment, supporting the household as a key epidemiological unit for malaria control and prevention in indigenous populations living in tropical regions.